Argentina : Request for Stand-By Arrangement and Request for Extension of Repurchase Expectations. (IMF Staff Country Reports; Country Report ;, 2003)
Good progress has been made in stabilizing the economic and social situation since the crisis. Fiscal adjustment over a prolonged period will bring the public finances to a sustainable path. To protect social expenditures and allow higher public investment, a comprehensive tax reform is required. Strengthening central bank autonomy is essential for the successful implementation of inflation targeting and restructuring of the financial system. Full cooperation with the multilateral development banks is important to secure necessary program financing, re-establishing sustained growth, and reducing widespread poverty.